Two new species of the Amphinemura luteipes species group (Plecoptera: Nemouridae) from Xizang, China - Kong, Xiangfei; Lin, Aili; Bozdoğan, Hakan; Yang, Ding; Li, Weihai (Zootaxa, 2025)
Two new stonefly species of the nemourid genus Amphinemura Ris, 1902, A. beibeng sp. nov. and A. pentaspina sp. nov., are described from the Xizang Autonomous region of southwestern China. The two new species are morphologically similar, their relationships are discussed, and the distribution of the A. luteipes species group is mapped and provided here.